2022
DOI: 10.3390/polym14050984
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquid Agar–Alginate Beads as a Sustainable Phenol Adsorbent

Abstract: Cleaning wastewater containing low concentrations of phenolic compounds is a challenging task. In this work, agar–alginate beads impregnated with trihexyltetradecylphosphonium bromide ([P66614][Br]) ionic liquid adsorbent were synthesized as a potential adsorbent for such applications. FTIR, TGA, SEM, EDX and PZC studies were performed to characterize and understand the physicochemical properties of the adsorbent. The Fourier transformation infrared spectroscopy (FTIR) study showed that [P66614][Br] ionic liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The TGA profile showed that thermal degradation of both the beads and the Na-alginate is increasing with the temperature. There are three phases for the degradation of the beads and Na-alginate [ 44 ]. The first phase lies between 50 to 120 °C, where a small amount of mass was decreased, which represents the removal of the moisture content [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The TGA profile showed that thermal degradation of both the beads and the Na-alginate is increasing with the temperature. There are three phases for the degradation of the beads and Na-alginate [ 44 ]. The first phase lies between 50 to 120 °C, where a small amount of mass was decreased, which represents the removal of the moisture content [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…There are three phases for the degradation of the beads and Na-alginate [ 44 ]. The first phase lies between 50 to 120 °C, where a small amount of mass was decreased, which represents the removal of the moisture content [ 44 ]. Once the temperature reached 200°C, an approximate 10% weight loss has been observed for the clay-alginate-ILs beads.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their versatility, ionic liquids (ILs) have been widely applied as extraction agents in recent years since they can be used as solvents for the dissolution of both organic and inorganic compounds, as well as chemical or electrochemical synthesis [15][16][17]. ILs are organic salts formed by bulky organic cations and small organic or inorganic anions, which remain in a liquid state below 373 K [18][19][20]. They have suitable properties such as high thermal and chemical stability and negligible vapor pressure, and it is possible to design them for a specific task, combining the cations and anions used in their obtention [21][22][23].…”
Section: Introductionmentioning
confidence: 99%